View of the Undeshwar Temple from the south - Temples of India Project Team (Jio Institute, 2024)
The Undeshwar Temple, devoted to Shiva, is oriented towards the west. It adopts a stellate layout, characteristic of the Bhumija architectural style. Resting upon elaborately carved, tall vedibandha (basal mouldings) serving as the foundation for the intricately carved jangha (wall), the temple features a Bhumija shikhara adorned with nine bhumis (storeys).